Legalism reconsidered: Weberian problems and Confucian solutions in the Han Feizi - Smith, Jackson T., author; Harris, Eirik Lang, advisor; Archie, Andre, committee member; Blanchard, Nathaniel, committee member (Colorado State University. Libraries, 2024)
After a thorough analysis of the political-philosophical climate of Warring States era China, I argue that Han Feizian Legalism is ultimately untenable on account of its necessarily sprawling bureaucratic apparatus which precludes adaptability and rapid response in the face of both internal and external crises. I show further that while Han Fei's criticisms of Confucianism are serious problems for the Confucian theorist, they are not vicious to generally cultivationist political theory. I go on to offer, through a synthesis of Confucian and Legalist doctrines, a solution which manages to patch the holes in both accounts and ultimately forge a broadly neo-classical approach to political organization, Legalism+, which relies on an epistemic naturalism à la Plato as the synthetic ground for Confucian and Legalist theory.
Keywords: classical Chinese philosophy; Max Weber; political realism; Han Feizi; Chinese philosophy; political philosophy